Salt use patterns and heavy metal urinary excretion - Zhang, Shuai; Tang, Hanhan; Zhou, Minglian; Pan, Linqing (Frontiers in Nutrition, 2025)
BackgroundSalt usage patterns have been associated with a risk of multiple diseases; however, their relationship with heavy metal exposure has not been extensively studied.MethodsThis study analyzed survey data from 11,574 NHANES participants. Weighted linear regression models were used to examine the relationship between the type of salt used by participants, the frequency of adding salt at the table, and the frequency of adding regular or seasoned salt to cooking or food preparation, and urinary concentrations of 10 heavy metals. Multiple sensitivity analyses were also performed.ResultsThe weighted regression analysis indicated that participants’ salt usage patterns were associated with an increased urinary excretion of certain heavy metals. Specifically, regarding the type of salt used, compared to regular salt, the use of salt substitutes was significantly positively correlated with urinary molybdenum (Mo) levels, while not using salt or substitutes at the table was significantly positively correlated with urinary levels of both Mo and arsenic (As). In terms of the frequency of adding regular salt at the table, frequent addition compared to rarely adding salt was significantly positively correlated with urinary levels of cadmium (Cd), and antimony (Sb), while showing a significant negative correlation with urinary Mo levels. Additionally, when examining the frequency of using regular salt during cooking or food preparation, those who occasionally or very often added regular salt had significantly higher urinary levels of barium (Ba), cesium (Cs), and thallium (Tl) compared to those who never added regular salt during cooking. These associations remained stable in sensitivity analyses.ConclusionOur analysis revealed that participants’ salt usage patterns are associated with increased excretion of certain heavy metals, suggesting possible increased exposures to these metals. While these findings are concerning, they require validation in other populations and should be confirmed through prospective studies designed based on this hypothesis.